2008
DOI: 10.1111/j.1365-2966.2008.12761.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term optical spectra variability of BL Lacertae object OJ 287

Abstract: Based on the long‐term data in the literature, we present evidence for long‐term optical spectral index variability behaviour for BL Lacertae object OJ 287. First we find that the optical spectral index variability period of BL Lacertae object OJ 287 is in agreement with the optical flux variability period of about 11.96 yr. It is considered that different processes induce optical variability, and each process should have a definite signature in the spectral index, thus leading to the periodicity of the spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…We have considered two fits to the corrected points: a power-law fit with spectral index of α = −0.4 ± 0.17 and a bremsstrahlung fit with temperature T = 3 +6 −2 × 10 5 K. The power-law fit would imply a spectrum which is flatter than the normal spectrum by ∆α ∼ 0.4 units. Such flattening of the spectrum at high brightness has been previously observed in other outbursts (Zheng et al 2008, Tavecchio et al 2010) even though by a smaller amount. In normal flares of OJ287 the whole spectrum up to optical-UV is raised, while the inverse Compton scattering in the relativistic jet raises the X-ray flux correspondingly (Seta et al 2009).…”
Section: Outburst Spectral Energy Distributionsupporting
confidence: 71%
“…We have considered two fits to the corrected points: a power-law fit with spectral index of α = −0.4 ± 0.17 and a bremsstrahlung fit with temperature T = 3 +6 −2 × 10 5 K. The power-law fit would imply a spectrum which is flatter than the normal spectrum by ∆α ∼ 0.4 units. Such flattening of the spectrum at high brightness has been previously observed in other outbursts (Zheng et al 2008, Tavecchio et al 2010) even though by a smaller amount. In normal flares of OJ287 the whole spectrum up to optical-UV is raised, while the inverse Compton scattering in the relativistic jet raises the X-ray flux correspondingly (Seta et al 2009).…”
Section: Outburst Spectral Energy Distributionsupporting
confidence: 71%
“…2 m . Zheng et al (2008) found that flux variations are associated with the color variations on long-term timescales. Then the color variations may be related with the active state of the object.…”
Section: Relation Of Color and Magnitudementioning
confidence: 99%
“…In Fig. 4, we show the observed time lag between 100-400 MeV and > 400 MeV with the discrete correlation function (DCF; Edelson & Krolik 1988;Zheng et al 2008). As can be seen that observed light curves do not show a significant time lag.…”
Section: Variability Profilementioning
confidence: 99%